2023
DOI: 10.3389/fsufs.2023.1141986
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable farming genes: spatial distribution and influencing factors of Chinese Agricultural Heritage Sites (CAHSs)

Abstract: Agricultural heritage is a fundamental aspect of cultural heritage, as it is of significant cultural, economic, and biological value. The objective of this study is to reveal the spatial distribution and change of the Chinese Agricultural Heritage Site (CAHS) by means of spatial analysis. The results show that: (1) The distribution of 532 CAHSs (7 types) is patchy, and the horticulture system is gaining the quantitative advantage (55.26%), (2) The distribution of CAHSs shows the spatial aggregation of “dense i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The presence of dense water systems and ample sunshine contribute to the growth of agricultural and animal husbandry, ensuring a stable livelihood for ethnic groups. Consequently, areas with plentiful water resources, ample sunlight, prosperous economies, and larger populations exhibit a higher prevalence of MHCSPL and NIAHS [32,45,46]. However, the single-factor analysis of annual average temperature and annual precipitation does not provide a strong explanation for the distribution of MCH in Southwest China.…”
Section: Natural Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of dense water systems and ample sunshine contribute to the growth of agricultural and animal husbandry, ensuring a stable livelihood for ethnic groups. Consequently, areas with plentiful water resources, ample sunlight, prosperous economies, and larger populations exhibit a higher prevalence of MHCSPL and NIAHS [32,45,46]. However, the single-factor analysis of annual average temperature and annual precipitation does not provide a strong explanation for the distribution of MCH in Southwest China.…”
Section: Natural Factorsmentioning
confidence: 99%
“…Previous studies have identified multiple variables that affect the formation and development of cultural heritage, such as natural, social, and economic factors [30,32]. This study examines the potential factors that may affect the outcome and divides them into two dimensions: natural factors (geography and climate) and human factors (population, economy, transportation, and culture).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations